2017
DOI: 10.1016/j.eml.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling large patterned deflection during lithiation of micro-structured silicon

Abstract: The application of silicon (Si) as potential anode material in Li-ion batteries provides a more than nine-fold increase in gravimetric storage capacity compared to conventional graphite anodes. However, full lithiation of Si induces the volume to increase by approximately 300%. Such enormous volume expansion causes large mechanical stress, resulting in non-elastic deformation and crack formation. This ultimately leads to anode failure and strong decrease in cycle life. This problem can be resolved by making us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, the dependence of mechanical properties on lithium concentration was not considered in this work. Laptev et al included this dependence during FEM modeling by ANSYS [18]. The appearance of plastic deformation during lithiation and bending of self-constrained honeycomb walls was predicted.…”
Section: Honeycomb-and Square-patterned Silicon Anodementioning
confidence: 99%
See 4 more Smart Citations
“…However, the dependence of mechanical properties on lithium concentration was not considered in this work. Laptev et al included this dependence during FEM modeling by ANSYS [18]. The appearance of plastic deformation during lithiation and bending of self-constrained honeycomb walls was predicted.…”
Section: Honeycomb-and Square-patterned Silicon Anodementioning
confidence: 99%
“…1b). Further optimization of honeycomb geometry has shown that the plastic deformation can be decreased or even eliminated, but only at the expense of a drastic reduction in footprint-area-specific storage capacity [18]. Subsequent analysis of the square-patterned microstructure storing the same energy per unit footprint-area has shown a lower -but still high -bending stress.…”
Section: Honeycomb-and Square-patterned Silicon Anodementioning
confidence: 99%
See 3 more Smart Citations